injauan Kelengkapan Pengisian Persetujuan Tindakan Kedokteran Pada Pasien Rawat Inap di Rumah Sakit Yadika Kebayoran Lama - Septia Salsabila; Indah Kristina; Rury Agnesia (MEDICORDHIF Jurnal Rekam Medis, 2018)
ABSTRACT The cause of death is any illness, illness, or injury that causes or facilitates the death and accident or violence that causes the injury. Medical certificate of cause of death is a certificate used to cause of death. From the obstervations at Setia Mitra Hospital there was not a single medical certificate of death which was filled in completely. The purpose of this study was to determine the completeness of filling in the death certificate medical certificate at Setia Mitra Hospital. The type of research used is descriptive. The method used is observation and intercview. The study population was 6 medical certificates causeing death. Based on the result of the quantitative analysis of the 6medical certificates that cause death, the results were completed in full by 76% and those that were not filled in were 24%. Of the four components of quantitative analysis, the most complete percentage analysis is found in the author authentication of 88,83% important report of 61,17%. Based on interviews conducted with medical record officers at Setia Mitra Hospital, there were several factors that caused incompleteness in filling out medical certificates for the cause of death, namely the absence of SPO (Standard Operating Procedures) which regulated the completeness of medical certificate of death cause and dthe implementation of quantitative analysis for medical causes. Death that has not yet been done. Keyword: Medical Certificat of Couse of Death